A new digital restoration technology of intracoronal color masking veneer - WANG Yu, GONG Yulin, XU Xiaobo, WANG Yuting, YU Fanfan (Kouqiang yixue)
The high permeability of glass ceramics limits the application of glass ceramics chair-side immediate restoration technology to pulp-free anterior teeth. This paper introduces a new digital intracoronary color-shielding veneer restoration technology, which uses computer-aided design/computer-aided manufacturing (CAD/CAM) technology to fabricate zirconia veneer in glass ceramics full crown, which can shield the influence of discolored abutments on the color of full crown and expand the clinical application range of high permeability glass ceramics.